Analysis of the Hujjah Level of Sahih and Hasan Hadiths - Maheningsih, Desi Dwi (Yayasan Sinergi Kawula Muda, 2023)
Hadith is the second source of law after the Qur'an. One of the functions of Hadith is as a place of interpretation, which aims to explain the verses of the Qur'an. To understand the law based on Hadith, one must know the Hadith Hujjahan. Judging from the quality of Hadith, it is divided into three parts, namely Sahih, Hasan, and Dhaif Hadith. However, this article aims to analyze only Sahih and Hasan Hadith. This research is literature research and falls into the category of qualitative research. The results of this study show that there are several choices of hadith degrees, which can be said to be sahih and hasan. Sahih if it meets the five conditions agreed upon by the scholars of hadith and Hasan if there are conditions that are not met. The highest evidence is Sahih hadith then Hasan hadith. Sahih hadith is divided into two types, namely Sahih Li-Dzatih and li-hair. There are also two types of hasan hadith, namely Hasan Li-Dzatih, and li-hair.